2012
DOI: 10.1262/jrd.2012-089
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effect of Hypoxia-Inducible Factor-1α on hCG-Stimulated Endothelin-2 Expression in Granulosa Cells from the PMSG-Treated Rat Ovary

Abstract: Abstract. Endothelin (ET)-2 plays a crucial role in ovarian ovulation in mammals. The present study was designed to test the hypothesis that hypoxia-inducible factor (HIF)-1α-mediated transcriptional activation contributes to the increased expression of ET-2 gene in response to hCG in rat ovarian granulosa cells (GCs) during gonadotropin-induced superovulation. By realtime RT-PCR analysis, ET-2 mRNA expression was found to significantly increase in cultured ovarian GCs after treatment with hCG, or even N-carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 30 publications
3
37
1
Order By: Relevance
“…In agreement with previous studies [23,25,26], we found that HIF1 is required for the regulation of Vegfa by LH in cultured granulosa cells. Unexpectedly however, granulosa cells isolated from Vegfa d/d ovaries 12 h post-hCG showed normal levels of Vegfa expression, indicating a normal response of the Vegfa gene to LH in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies [23,25,26], we found that HIF1 is required for the regulation of Vegfa by LH in cultured granulosa cells. Unexpectedly however, granulosa cells isolated from Vegfa d/d ovaries 12 h post-hCG showed normal levels of Vegfa expression, indicating a normal response of the Vegfa gene to LH in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…1B). Together, these results confirm the previously reported [21][22][23][24][25][26] requirement of HIF1 for gonadotropin-regulated Vegfa expression in granulosa cells and pinpoint a single HRE in the Vegfa promoter that is required for HIF1-mediated regulation of Vegfa transcription and gonadotropin responsiveness in granulosa cells in vitro.…”
Section: Hif1 Acts Through a Single Hre In The Vegfa Promoter To Medisupporting
confidence: 91%
See 1 more Smart Citation
“…3) Granulosa cell culture experiment (Zhang et al, 2012a): granulosa cells were isolated from immature rat ovaries and cultured with HIF-1α small interfering RNA (siRNA) and scrambled siRNA transfection.…”
Section: Experimental Designmentioning
confidence: 99%
“…When cell fusion was approximately 85%, siRNA transfection was performed using the siLentFect Lipid Reagent (Bio-Rad) according to manufacturer instructions (Zhang et al, 2012a). For a 10-cm dish, 200 pmol siRNA was used.…”
Section: Transfection Of Hif-1α Sirnamentioning
confidence: 99%